The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0101-31222009000200022
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica de sementes de beterraba (Beta vulgaris L.) sob condicionamento osmótico e tratamentos fungicidas

Abstract: -The osmotic conditioning and fungicide treatments of seeds have presented good results in vigor improvement and seedling protection against microorganisms associated to the seeds and soil, thus guaranteeing good stand establishment. The objective of this study was to evaluate the effect of osmotic conditioning and fungicide treatment on the physiological quality of beet seeds. The seeds were conditioned in water, KNO 3 (0.34 M), PEG 6000 (-0.8 MPa). The treatments with fungicides were: control (seeds treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Dias et al (2009) found that beet seeds exposed to osmotic conditioning in water for 16 h, followed by fungicide treatment (0.004% Metalaxyl) had the most positive influence in the germination test and on the establishment of seedlings in soil, among the treatments studied.…”
mentioning
confidence: 94%
“…Dias et al (2009) found that beet seeds exposed to osmotic conditioning in water for 16 h, followed by fungicide treatment (0.004% Metalaxyl) had the most positive influence in the germination test and on the establishment of seedlings in soil, among the treatments studied.…”
mentioning
confidence: 94%
“…Dias et al (2009) have affirmed that seed treatment with fungicide are recommendable for seeds submitted to priming, once such practice favor maintenance of the seed quality. There was no interaction between seedling emergence and seedling emergence speed index, and, so, both treatments were independent for these two parameters (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…The castor bean seeds naturally have a slow and uneven germination, which extends their expousure to soil pathogens and other environmental stresses, resulting in irregular stands. Therefore, the use of seeds with high germination rates and vigor guarantees producers success regarding proper stand establishment (Dias et al 2009). …”
Section: Introductionmentioning
confidence: 99%